Mekong Riverfront Cultural Public Spaces in Nakhon Phanom City, Thailand - Methee Piriyakarnnon; Nopadon Thungsakul (Journal of Mekong Societies, 2025)
This study explores the cultural public spaces of Nakhon Phanom city, examining the relationship between culture and public space. It encompasses physical, public, and cultural components, ethnic groups, and the significance of culture in public spaces. The analysis covers management and development, cultural changes in space management, and an examination of cultural factors influencing public spaces. The study aims to summarize the diverse characteristics of cultural public spaces in Nakhon Phanom and highlight their importance in the city. Findings indicate that the Mekong Riverfront intertwines traditional, contemporary, and mixed cultures. It features physical potential, diverse cultural activities, and distinct periods. The area has gained cultural significance through societal processes, reflecting use patterns, perception, and management. It has also undergone noticeable physical transformations over time.